Holocene palaeoenvironmental changes in the Thar Desert: an integrated assessment incorporating new insights from aeolian systems - Srivastava, A; Thomas, DSG; Durcan, JA; Bailey, RM (Elsevier, 2020)
Due to the scarcity of geochemical and palaeoecological proxies in drylands, dunes have often been used as geoproxies for late Quaternary palaeoenvironmental reconstruction, with chronologies commonly provided by luminescence dating. Owing to their widespread occurrence and location in a monsoonal regime, dunes in the Thar Desert in South Asia act as important archives of past landscape change. Previous reviews have assimilated dune age data from the Thar and suggested a temporally and spatially complex record of sediment accumulation over the last ∼70 ka. New luminescence age data presented in this study and from recent dunefield based investigations demonstrate a stronger Holocene record of dune building in parts of the Thar than previously suggested. In this study, the Accumulation Intensity (AI) methodology is applied to new and old data sets, providing records of dune accumulation that can be analysed alongside other palaeoenvironmental records. AI analysis demonstrates the significance of Holocene dune accumulation in the Thar landscape, with accumulation peaks observed between ∼12 and ∼8 ka, centred around ∼7, ∼5 and ∼3.5 ka, and in last two millennia. The strengthening of the Indian Summer Monsoon remains a significant influence on widespread dune accumulation in the early Holocene, but dunefields have also shown diverse and spatially intensive responses to sediment supply and anthropogenic disturbances during the late Holocene. Additionally, aeolian-fluvial sequences associated with the Ghaggar-Hakra palaeochannel along the northern margin of the Thar also display dynamic geomorphic behaviour during the Holocene. The integration and interpretation of the AI data with published, highly resolved geochemical proxies of palaeoclimate, shows a complex relationship between geoproxy and geochemical records. We suggest that process studies of geomorphologic systems and their diverse responses to the same environmental stimuli must be given due consideration before deriving palaeoenvironmental interpretations. Despite the presence of over a hundred Holocene dune records from the Thar, there still remains marked spatial and temporal gaps. Further intensive investigations of distinct dunefields with a strong chronometric framework and geomorphological grasp are required to gain significant insights into wider Thar landscape and palaeoenvironmental dynamics.